Bifocal and Multifocal Contact Lenses for Presbyopia and Myopia Control - Laura Remón; Pablo Pérez-Merino; Rute J. Macedo-de-Araújo; Ana I. Amorim-de-Sousa; José M. González-Méijome (Journal of Ophthalmology)
Bifocal and multifocal optical devices are intended to get images into focus from objects placed at different distances from the observer. Spectacles, contact lenses, and intraocular lenses can meet the requirements to provide such a solution. Contact lenses provide unique characteristics as a platform for implementing bifocality and multifocality. Compared to spectacles, they are closer to the eye, providing a wider field of view, less distortion, and their use is more consistent as they are not so easily removed along the day. In addition, contact lenses are also minimally invasive, can be easily exchangeable, and, therefore, suitable for conditions in which surgical procedures are not indicated. Contact lenses can remain centered with the eye despite eye movements, providing the possibility for simultaneous imaging from different object distances. The main current indications for bifocal and multifocal contact lenses include presbyopia correction in adult population and myopia control in children. Considering the large numbers of potential candidates for optical correction of presbyopia and the demographic trends in myopia, the potential impact of contact lenses for presbyopia and myopia applications is undoubtedly tremendous. However, the ocular characteristics and expectations vary significantly between young and older candidates and impose different challenges in fitting bifocal and multifocal contact lenses for the correction of presbyopia and myopia control. This review presents the recent developments in material platforms, optical designs, simulated visual performance, and the clinical performance assessment of bifocal and multifocal contact lenses for presbyopia correction and/or myopia progression control.